Sporcularda ani ölüm - (:unkn) unknown (My University, 2006)
Son yıllarda giderek artan sayıda çocuk ve ergen spor etkinliklerine katılmaktadır, ancak karşılaşma ya da antreman sırasında meydana gelen ani ölümler aile ve toplumda endişe yaratmaktadır. Ani ölümlerin %95'i kalbe ait nedenlerle meydana gelmektedir. En sık nedenler hipertrofik kardiyomiyopati, aritmojenik sağ ventrikül displazisi, doğuştan koroner arter anomalileridir. Tanı almış ya da tanı almamış kalp hastalıklarının yanısıra basan artırıcı maddelerin etkisinden de sözedilebilir. Ani ölümlerin önlenebilmesi için tüm sporculara standart tarama programlarının uygulanması gereklidir. İyi bir öykü, aile öyküsü ve fizik muayenenin yanısıra elektrokardiyografi ile değerlendirme birçok kalp hastalığının dışlanmasını sağlayacaktır.

Increasing number of children and adolescents are involved in sportive activities in recent years. However, sudden death of some young athletes causes anxiety among the parents and the society. About 95% of sudden deaths are related to the cardiac causes. The most common disease states are hypertrophic cardiomyopathy, arrhythmogenic right ventricle displasia, and congenital abnormalities of the coronary arteries. In addition to heart disease whether diagnosed or not, the effect of performance enhancing substances must also be considered. In order to prevent sudden death, standard screening programs should be applied to all athletes. A detailed history including the family history, physical examination and electrocardiography would provide exclusion of many cardiac disorders.
Sudden death in athletes
Keywords: Kalp ve Kalp Damar Sistemi